THE SIGNIFICANCE OF WEBSITE INTERACTIVITY AND AUGMENTED REALITY ON ATTITUDE TOWARDS WEBSITE AND MOBILE DEVICE INTERACTIVITY IN COSMETICS RETAILING - L. A, Clark; Watson , D; Reynolds, S (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
Corporate governance has been extensively studied since the 1980s, and the effectiveness of governance mechanisms in aligning firm interests with shareholders’ interests and improving performance has been a topic of interest for scholars. However, most studies have focused on Anglo-Saxon contexts, and it remains unclear whether these governance mechanisms will be effective in countries with weak shareholder protection and underdeveloped financial markets. This study examines corporate governance mechanisms suitable for small and medium-sized enterprises (SMEs) in Morocco, a country where more than 95 percent of businesses are SMEs, and reviews the effectiveness of these mechanisms in improving export performance. The study highlights the critical role of SMEs in generating value, creating jobs, and contributing to local development in Morocco. The concentration of ownership among families and the fierce competition in the money market necessitate modernization and differentiation through human resources. Export is an essential strategy for SMEs to access international markets and hasten the internationalization process. The study presents a literature review to identify corporate governance mechanisms applicable to Moroccan exporting SMEs and assesses the effectiveness of these mechanisms in terms of export performance. The study contributes to the literature by unraveling governance mechanisms suitable for SMEs in emerging economies and highlighting the importance of corporate governance in enhancing SME export performance.